2010
DOI: 10.1111/j.1365-2036.2010.04410.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: levamisole improves the immune response to hepatitis B vaccine in dialysis patients

Abstract: SUMMARY BackgroundPatients undergoing maintenance dialysis often fail to mount protective antibodies to hepatitis B virus surface antigen (HBsAg) following vaccination against hepatitis B virus (HBV). Some authors have suggested that levamisole improves immune response to HBV vaccine in dialysis population. However, consistent information on this issue does not exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Levamisole, a synthetic phenylimidazolthiazole with an antihelminthic effect, has been reported to stimulate depressed T-cell activity and enhance the production of antibodies by B cells (7475). In addition, Chen et al demonstrated that the treatment of monocyte-derived DCs from healthy donors with levamisole increased the presentation of CD80, CD86, CD83 and MHC class II molecules on the cell membrane and the production of IL-12 p40.…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Levamisole, a synthetic phenylimidazolthiazole with an antihelminthic effect, has been reported to stimulate depressed T-cell activity and enhance the production of antibodies by B cells (7475). In addition, Chen et al demonstrated that the treatment of monocyte-derived DCs from healthy donors with levamisole increased the presentation of CD80, CD86, CD83 and MHC class II molecules on the cell membrane and the production of IL-12 p40.…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
“…Moreover, a meta-analysis of four studies (328 patients) showed that the oral administration of levamisole at a dose of 80~120 mg for 4~6 months significantly increased seroconversion after HBV vaccination (75). These observations suggest that levamisole could significantly improve the response rates of patients on HD to several vaccines through, at least in part, activating DCs.…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
“…Most of the published systematic reviews on this subject have been performed by Fabrizi et al [31] investigating potential effects of a large number of factors on HBV vaccination in dialysis patients. For example they found no significant effects for using erythropoetin (Epo) [31] and some other adjuvants [32] on the immunogeneity of HB vaccination in kidney disease patients; while several other factors significantly associated with seroconversion have also been reported by the same authors that included use of levamisole [33] , granulocyte macrophage-colony stimulating factor [32] and thymopentin use [34] . Seroresponse of patients on maintenance hemodialysis vs peritoneal dialysis …”
Section: Discussionmentioning
confidence: 90%
“…2), in the literature, have been considered to be adaptogens. Dibazol’s adaptogenic action was first realized in the context of immune-mechanism-enabled adaptation to difficult environmental conditions (Rusin, 1962a, 1962b, 1963a, 1963b, 1963c, 1967; Ratnikov and Nesterenko, 1984; Novikov and Bortnovskii, 1985; Udintsev et al ., 1991; Sidorova and Kiikova, 2000); levamisole’s adaptogenic activity also is connected primarily with adaptive immune system changes (Voskanian et al ., 1986; Alvarez-Pellitero et al ., 2006; Chen et al ., 2008; Fabrizi et al ., 2010); afobazol has neuroprotective properties established, in vitro , by survival of HT-22 neurons in a model of oxidative stress and glutamate toxicity (Zenina et al ., 2005), and its adaptogenic action is realized through central nervous system adaptation (Uyanaev and Fisenko, 2006; Litvintsev et al ., 2007; Bogdan et al ., 2011). As reflects their adaptogenic properties, benzimidazole derivatives are related to bemitil, but their influence on physical work capacity is either absent or minimal.…”
Section: Definition and Classification Of Actoprotectorsmentioning
confidence: 99%